Development of barium hexaferrite core–shell composites as high-performance microwave absorption by optimizing hydrothermal synthesis - Yustanti, Erlina; Noviyanto, Alfian; Fauziah, Annisa Nur; Lubis, Bachtiar; Trenggono, Adhitya; Taufiq, Ahmad (Eastern-European Journal of Enterprise Technologies, 2023)
In conjunction with the enhancement of societal living standards and the rapid development of information technology, an extensive variety of high-capacity electronic devices are being introduced to the market. The heightened demands result in the generation of electromagnetic wave radiation, which poses a potential risk to human well-being. Barium hexaferrite (BHF) is one of the radar-absorbing materials (RAMs) that can absorb electromagnetic waves because it has a high anisotropic field. However, its drawbacks are narrow absorption and less stability. Molybdenum disulfide (MoS2), is the best candidate for the reinforcement of BHF. The study investigated the impact of increasing the thiourea, temperature, hydrothermal holding time, and sample thickness on reflection loss. This study used a two-step molten salt and hydrothermal synthesis to make a BaFe12O19@MoS2 core-cell composite. Two-step molten salt and hydrothermal synthesis methods created single-phase BaFe12O19@MoS2 core-cell composites that worked well. The results showed that adding MoS2 to BHF changed BHF's magnetic properties from hard to soft. Increasing the hydrothermal temperature up to 220 °C effectively reduced the reflection loss of BaFe12O19@MoS2. On a 2 mm thick sample containing 100 mmol thiourea, the study achieved an electromagnetic wave absorption of 99.97 % with a reflection loss of –35.41 dB (17.37 GHz). The results of this research can be applied to protect electronic devices vulnerable to signal interference from satellite radar systems at frequencies of 12–18 GHz